Public spaces as political spaces: what does it mean? - de Castro, Iná Elias (Geografares, 2018)
This article proposes to discuss the conditions for the transformation of public spaces into political spaces and to respond how this occurs. The thesis defended is that public spaces are spaces of everyday urban social and do not have a political essence, although they may become political spaces when invaded by phenomena of politics that temporarily transform their routines and their usual public. The text is divided into three parts. In the first, politics is conceptualized as an institutional and operational system for resolving conflicts of interest, presenting the risks of the fallacy, very common in the sociological literature, of considering politics as an abstract sphere. In the second, the political space is presented as a concept, that despite the origin in political science, was appropriated and expanded in political geography as a space for action of public policies and laws, but also for social movements and political acts. In the third part, the arguments of the central thesis of this text are elaborated, answering the question about the circumstances in which the public spaces can turn into political spaces.Keywords: Political space; public space; political mobilizations.